Efektivitas Bermain Pada Masa Pendidikan Anak Usia Dini di PAUD Al-Mahir - Rasti Purnamasari; Leni Masnidar Nasution; Khairuddin YM (Prodi PIAUD STAI Sumatera Medan, 2021)
Early childhood education is very meaningful for child development. The method used must be in accordance with the child's development, the method used is playing. The reality is that in children's life it is inseparable from playing, from playing children to get extraordinary experiences. This research was conducted in a qualitative form. The purpose of this paper is to determine the effectiveness of play in early childhood education. The results of this study are proven that playing can affect early childhood education